2018
DOI: 10.1111/imm.12940
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA expression profile and potential function of hsa_circ_0045272 in systemic lupus erythematosus

Abstract: Circular RNAs (circRNAs) represent a class of non-coding RNAs that form covalently closed RNA circles with extensive expression and conservation in mammals. Circular RNAs regulate gene expression through acting as competitive endogenous RNAs (ceRNAs) and modulating gene transcription. Accumulating evidence supports the implication of circRNAs in a variety of human diseases, but studies of circRNA role in systemic lupus erythematosus (SLE) are lacking. The present study measured the circRNA expression profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 55 publications
0
56
0
1
Order By: Relevance
“…Thus, it was speculated that the dE circRNAs or miRNAs associated with blood loss could also be correlated with ONFH. Third, the dE circRNAs and miRNAs might also result from the autoimmune diseases such as SLE instead of ONFH, which has been demonstrated in previous studies (44)(45)(46). It is true that SLE itself could lead to DE miRNAs and circRNAs.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, it was speculated that the dE circRNAs or miRNAs associated with blood loss could also be correlated with ONFH. Third, the dE circRNAs and miRNAs might also result from the autoimmune diseases such as SLE instead of ONFH, which has been demonstrated in previous studies (44)(45)(46). It is true that SLE itself could lead to DE miRNAs and circRNAs.…”
Section: Discussionmentioning
confidence: 75%
“…Among those identified, decreased circ_0045272 expression was observed in T cells from SLE patients. Downregulation of the circ_0045272 in Jurkat cells induced early apoptosis and significantly enhanced IL-2 production [ 60 ], features of SLE onset.…”
Section: Role Of Ncrnas In Systemic Lupus Erythematosusmentioning
confidence: 99%
“…They found hsa_circ_0045272 to be downregulated significantly. Furthermore, they demonstrated that hsa_circ_0045272 regulated apoptosis and IL-2 production negatively (89). However, the mechanisms underlying the involvement of hsa_circ_0045272 in SLE pathogenesis merits further exploration.…”
Section: Circrnas In Immunitymentioning
confidence: 99%